2023
DOI: 10.1007/s00238-023-02050-8
|View full text |Cite
|
Sign up to set email alerts
|

Role for platelet rich plasma as an adjuvant therapy in wound healing and burns

Abstract: Background Platelet rich plasma (PRP) contains high concentrations of growth factors. Intuitively, these were thought to be of potential benefit in healing of chronic wounds, skin grafts and graft donor sites. This was echoed in retrospective studies and an individual case basis but had not been randomized. Methods A systematic search was carried out by two individuals, independently, on the MEDLINE, EMBASE and COCHRANE databases, according to PRISMA guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Injections of autologous PRP were administered to a patient with a scar from BWs once a month for 6 months, according to Ruiz et al Particularly after 180 days of treatment, they observed significant changes in pliability, vascularity, discomfort, irregularity and colour 7 . PRP exhibits antibacterial effects against some bacterial strains, but not all of them, according to in vitro investigations 32–36 . Bacterial infection or discomfort was reported to be indistinguishable between PRP and control wounds in an RCT including 20 consecutive leg ulcer patients who received a single application of topical platelet‐rich fibrin 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injections of autologous PRP were administered to a patient with a scar from BWs once a month for 6 months, according to Ruiz et al Particularly after 180 days of treatment, they observed significant changes in pliability, vascularity, discomfort, irregularity and colour 7 . PRP exhibits antibacterial effects against some bacterial strains, but not all of them, according to in vitro investigations 32–36 . Bacterial infection or discomfort was reported to be indistinguishable between PRP and control wounds in an RCT including 20 consecutive leg ulcer patients who received a single application of topical platelet‐rich fibrin 29 …”
Section: Discussionmentioning
confidence: 99%
“…7 PRP exhibits antibacterial effects against some bacterial strains, but not all of them, according to in vitro investigations. [32][33][34][35][36] Bacterial infection or discomfort was reported to be indistinguishable between PRP and control wounds in an RCT including 20 consecutive leg ulcer patients who received a single application of topical platelet-rich fibrin. 29 Limitations of the meta-analysis were as follows: there could be an assortment bias because some of the examinations that were chosen for the meta-analysis were excluded.…”
Section: Study or Subgroupmentioning
confidence: 99%
“…However, existing evidence does not strongly endorse the use of PRP as an adjuvant therapy in various contexts, including skin grafts, burns, carpal tunnel surgery, or scars. A study proposed that while PRP may potentially enhance split-thickness skin graft donor site healing, the overall morbidity from the donor site remains low, posing a challenge in justifying the use of PRP from a health economics perspective [ 41 ]. Moreover, a systematic literature review on split-thickness skin graft donor-site morbidity emphasized the diverse outcomes under evaluation, ranging from time to healing and pain intensity to hypertrophic scarring, infections, pruritus, and stiffness [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, current evidence does not robustly support using specific adjuvants, such as platelet-rich plasma (PRP), in various contexts like skin grafts, burns, carpal tunnel surgery, or scars. The potential benefits of PRP, even in expediting split-thickness donor site healing, are challenged by the overall low morbidity from the donor site, creating difficulties in justifying its use based on health economics considerations [ 41 ]. Donor site morbidity in skin transfer techniques encompasses a range of outcomes, including pain, discomfort, infections, pruritus, wound exudation, and aesthetic dissatisfaction [ 40 ].…”
Section: Reviewmentioning
confidence: 99%
“…It inhibits the production of cytokines and reduce inflammation by activation of macrophages to enhance tissue repair and regeneration, encourage the creation of new capillaries, and quickening the epithelialization process in chronic wounds (9) . This study aimed to compare the beneficial role of BM-MSCs versus PRP in skin burn management.…”
Section: Introductionmentioning
confidence: 99%